Pengaruh Model Pembelajaran Discovery Learning Berbantuan E-LKPD Terhadap Hasil Belajar Peserta Didik pada Materi Usaha dan Energi Kelas X Smanegeri 1 Percut SEI Tuan - Kartini Anggi Agata Sihotang; Muhammad Kadri (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to determine the effect of the Discovery Learning model assisted by E-LKPD on students' physics learning outcomes. The research was conducted at SMA Negeri 1 Percut Sei Tuan. This type of research is a quasi-experimental design with a pretest-posttest control group design. The sampling technique used in this study was cluster random sampling, consisting of an experimental class and a control class, each with 36 students. The solution to address the research problem was to apply the Discovery Learning model assisted by E-LKPD in the experimental class and conventional learning in the control class. The subjects of this study were students in classes X-3 and X-4. The instrument used was a learning test in the form of 15 multiple-choice questions. Before the different treatments were applied, a pretest was conducted, resulting in an average pretest score of 48.1 for the experimental class and 45.6 for the control class. Normality and homogeneity tests on the pretest data indicated that both classes' data were normally distributed and homogeneous. The two-tailed t-test resulted in a value of tcount < ttabel = = 0.97 < 1.994, which means H0 was accepted, indicating that the initial critical thinking ability of the experimental and control classes was the same. After the different treatments, a posttest was conducted for both classes, which resulted in an average posttest score of 76.5 for the experimental class and 63.5 for the control class. Normality and homogeneity tests on the posttest data showed that both classes' data were normally distributed and homogeneous. The one-tailed t-test resulted in tcount < ttabel = = 4.860 > 1.666, so the alternative hypothesis (Ha) was accepted. It can be concluded that the use of Discovery Learning assisted by E-LKPD has a significant effect on students' learning outcomes on the topic of work and energy in class X at SMA Negeri 1 Percut Sei Tuan.